Study on Reservoir Properties and Critical Depth in Deep Coal Seams in Qinshui Basin, China. (2nd June 2019) - Zheng, Guiqiang; Sun, Bin; Lv, Dawei; Pan, Zhejun; Lian, Huiqing
Abstract : Coalbed methane (CBM) reservoir properties and relationship of properties with burial depth were studied based on the data derived from 204 deep CBM production wells in Qinshui Basin, China. Through the study, it is found that permeability and porosity decrease with the increase of burial depth and the decreasing trend shows step-change characteristics at a critical burial depth. They also show divisional characteristics at certain burial depth. Gas content, geostress, and geotemperature increase with the increase of burial depth, and the increasing trend shows step-change characteristics and also have divisional characteristics at certain burial depth. Based on the previous study on the reservoir property changes with burial depth, three series of critical depth using different parameters are obtained through simulating the critical depth using the BP neural network method. It is found that the critical depth is different when using different parameters. Combined the previous study with the normalization of three different parameter types, the critical depth in Qinshui Basin was defined as shallow coal seam is lower than 650 m and transition band is 650–1000 m, while deep coal seam is deeper than 1000 m. In deep coal seams, the geological conditions and recovery becomes poor, so it can be defined as unfavorable zones. Therefore, other development means, for example, CO2 injection, need to be used to accelerate the deep coal methane development.